CIOA: Circle-Inspired Optimization Algorithm, an algorithm for engineering optimization - Otávio Augusto Peter de Souza; Letícia Fleck Fadel Miguel (SoftwareX, 2022)
This paper presents a new, robust and very efficient metaheuristic optimization algorithm, called Circle Inspired Optimization Algorithm (CIOA), for solving constrained and unconstrained engineering optimization problems. The inspiration for the proposed algorithm consists of well-known formulations of the trigonometric circle. CIOA is compared with five other very famous algorithms in ten benchmark function optimization problems, five real-world engineering constrained optimization problems, and also four structural optimization problems for plane and spatial trusses subjected to multiple and different types of constraints. The results obtained demonstrate that the proposed algorithm is more efficient than other famous algorithms, contributing to the accurate and fast solution of complex optimization problems.